2017
DOI: 10.18632/oncotarget.21628
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 promotes tumor-like invasion of fibroblast-like synoviocytes in rheumatoid arthritis via targeting TIMP1

Abstract: Suppression of tissue inhibitor of matrix metalloproteinase (TIMP) is associated with the tumor-like invasion of fibroblast-like synoviocytes (FLSs) that occurs during rheumatoid arthritis-related cartilage destruction. Silent information regulator 2 homolog1 (SIRT1), a histone deacetylase, is widely involved in transcriptional regulation, genomic stability, metabolism and DNA repair. Recent studies suggest that SIRT1 may also impact inflammatory response and the proliferation of FLSs in rheumatoid arthritis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…Previously, it was reported that IL-10 works as an anti-in ammatory cytokine, inhibits VEGF [41], and suppresses in ammatory response [42]. The increased Timp1 has been reported to ameliorate cartilage destruction in collagen-induced arthritis in rats [43]. All these ndings are in accordance with our hypothesis that the amino acid transporter SLC7A5 takes part in cellular invasion and regulates protein levels of MMP3 and MMP13 via mTOR signaling pathway in RA FLS.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, it was reported that IL-10 works as an anti-in ammatory cytokine, inhibits VEGF [41], and suppresses in ammatory response [42]. The increased Timp1 has been reported to ameliorate cartilage destruction in collagen-induced arthritis in rats [43]. All these ndings are in accordance with our hypothesis that the amino acid transporter SLC7A5 takes part in cellular invasion and regulates protein levels of MMP3 and MMP13 via mTOR signaling pathway in RA FLS.…”
Section: Discussionsupporting
confidence: 90%
“…Previous literature reported that these cytokines, like IL-10 works as an anti-inflammatory cytokine, inhibits VEGF [37], decrease the inflammatory responses [38]. The increased Timp1 could ameliorate cartilage destruction in collagen-induced arthritis in rats [39]. All these findings are accord with our hypothesis that the amino acid transport SLC7A5 took part in invasion via regulating the protein expression of MMP3 and MMP13 in RA FLS.…”
Section: Discussionsupporting
confidence: 89%
“…Synovial hyperplasia is frequently seen in RA synovium, which results from the accumulation of FLSs and MLSs in a specific inflammatory microenvironment [ 12 14 ]. RA FLSs display cancerous properties in inflamed synovial tissue, whereby they exhibit local tumor-like destructive and invasive characteristics [ 15 , 16 ]. The phenotype, behavior, and role of FLSs in RA resemble the fundamental role of cancer-associated fibroblasts (CAFs) in various cancers [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%